Pneumococcal Septicemia after COVID-19 in Teenager: Clinical Case - Viktor V. Krasnov; Danila A. Pimenov; Valery I. Sedov; Vera N. Kotova; Lilia R. Pavlovich (Педиатрическая фармакология)
There is a hypothesis among the scientists that COVID-19 and SARS-CoV-2 have negative effect on the immune system. Many reports on multisystem inflammatory syndrome (MIS) development after COVID-19 are published worldwide. Whereas, the impact of this infection on prevalence and course of any other infectious diseases has not been studied. The aim of the study is to draw attention to the estimation of other infectious diseases course after COVID-19 by analyzing the clinical case of pneumococcal septicemia in 17 years old boy who has undergone COVID-19. We obtained data about COVID-19 during the analysis of the child's medical history. The course of infectious process was similar to the course of multisystem inflammatory syndrome in children (MIS-C), compared by clinical manifestations. The results of ELISA blood assay have proved it: we revealed IgG to SARS-CoV-2. However, PCR test revealed S. pneumoniae DNA in blood, so MIS-C diagnosis was excluded. The role of SARS-CoV-2 in other diseases in postcovid period can not be excluded, and it requires further studies. Development of screening and rehabilitation principles is recommended despite the severity of COVID-19 in children.